VCP/p97 cofactor UBXN1/SAKS1 regulates mitophagy by modulating MFN2 removal from mitochondria. Issue 1 (2nd January 2022) - Mengus, Chantal; Neutzner, Melanie; Bento, Ana Catarina Pinho Ferreira; Bippes, Claudia C.; Kohler, Corina; Decembrini, Sarah; Häusel, Jessica; Hemion, Charles; Sironi, Lara; Frank, Stephan; Scholl, Hendrik P. N.; Neutzner, Albert
ABSTRACT: Initiation of PINK1- and PRKN-dependent mitophagy is a highly regulated process involving the activity of the AAA-ATPase VCP/p97, a cofactor-guided multifunctional protein central to handling ubiquitinated client proteins. Removal of ubiquitinated substrates such as the mitofusin MFN2 from the outer mitochondrial membrane by VCP is critical for PRKN accumulation on mitochondria, which drives mitophagy. Here we characterize the role of the UBA and UBX-domain containing VCP cofactor UBXN1/SAKS1 during mitophagy. Following mitochondrial depolarization and depending on PRKN, UBXN1 translocated alongside VCP to mitochondria. Prior to mitophagy, loss of UBXN1 led to mitochondrial fragmentation, diminished ATP production, and impaired ER-mitochondrial apposition. When mitophagy was induced in cells lacking UBXN1, mitochondrial translocation of VCP and PRKN was impaired, diminishing mitophagic flux. In addition, UBXN1 physically interacted with PRKN in a UBX-domain depending manner. Interestingly, ectopic expression of the pro-mitophagic VCP cofactor UBXN6/UBXD1 fully reversed impaired PRKN recruitment in UBXN1 -/- cells. Mechanistically, UBXN1 acted downstream of PINK1 by facilitating MFN2 removal from mitochondria. In UBXN1 -/- cells exposed to mitochondrial stress, MFN2 formed para-mitochondrial blobs likely representing blocked intermediates of the MFN2 removal process partly reversible by expression of UBXN6 . Presence of these MFN2 blobs strongly correlated with impaired PRKN translocation to depolarized mitochondria. Our observations connect the VCP cofactor UBXN1 to the initiation and maintenance phase of PRKN-dependent mitophagy, and indicate that, upon mitochondrial stress induction, MFN2 removal from mitochondria occurs through a specialized process.